QORAQALPOG‘ISTON TURKMANLARI TILINING O‘RGANILISHI TARIXI - Babayeva, M.A.; Qutibaeva, A. (SCIENCE and SOCIETY, 2023)
This article describes the history of the study of the Turkmen language and phonetic, morphological changes occurring in the language, issues of bilingualism of the language, as well as several works on the Turkmen language.
Keywords: the Uzbek language; the Karakalpak language; history of the Turkmen language; problems of bilingualism